Reactions of Students Towards Class Cancellation, Class Rescheduling, Inadequate Classes and Classes for Less Than Designated Duration in Dhaka University - Uddin, Muhammad Kamal; Rahman, Jakia; Zaman, Tazbina; Ahsan, Khadiza (Dhaka University Journal of Biological Sciences, 2023)
A serious departure from the norm in taking classes has been a regular phenomenon in the University of Dhaka in recent years. The present study aimed to investigate perceptions, reactions, and grievances of students towards class cancellation, class rescheduling, inadequate classes, and classes for less than duration at the University of Dhaka. Data were collected online from 522 students (51.5% male and 48.5% female, mean age = 21.74 years) of the university using a mixed-method design. The quantitative data were analyzed by t-test, Chi-square test, and Pearson product-moment correlation coefficients in SPSS version 24. The results of the t-test demonstrated no significant gender differences in perception towards the main variables. The Chi-square test reveals that the frequencies of occurrences of these phenomena significantly differ among the faculties of four hierarchical positions. The content analysis of the qualitative data revealed 12 major themes namely the four factors across academic units, the favorable impact of these phenomena, increased absenteeism, the sources of stress, anxiety, and frustration, lack of priority, teachers’ disinterest in teaching and learning, a sense of punctuality and responsibility, mutual understanding, timetable of the rescheduled classes, teacher’s accountability and students’ feedback, introducing training for teachers, and the role of authority. The findings of the study suggest a clear lack of administrative control over the teaching behavior of the faculties. The study recommends that the university authority should immediately address these issues to redress the grievances of the students and thereby ensure a quality culture in teaching, learning and research. Dhaka Univ. J. Biol. Sci. 31(2): 309-319, 2022 (July)